Women and care: disputes and negotiations in academic space - Rosas Rodríguez, Ana María (2020)
This article offers both empirical and theoretical resources that demonstrate how the link between space and gender operates in academic life in social sciences and humanities in Bogotá, Colombia. By examining ten life stories of women who work in different universities, we affirm that academia is a hostile space for the women who inhabit it, as it reproduces dualist, colonial, hetero-patriarchal and capitalist logics within it; these particularly affect the experiences of women and non-heteronormative bodies. Care is found to be a central and conflictive notion in this experience of academia, as it operates both as a form of oppression, by nullifying women’s participation and visibility, and as a form of resistance, negotiation and political power to transform the university.